How does climate change alter agricultural strategies to support food security? Some comments - Andrew, Dale (2013)
Priorities for Public Sector Research on Food Security and Climate Change, Review 1 by Dale Andrew, OECD on April 12, 2013 at the Food Security Futures Conference in Dublin, Ireland.